GAD2 Alternative Transcripts in the Human Prefrontal Cortex, and in Schizophrenia and Affective Disorders - Davis, Kasey N.; Tao, Ran; Li, Chao; Gao, Yuan; Gondré-Lewis, Marjorie C.; Lipska, Barbara K.; Shin, Joo Heon; Xie, Bin; Ye, Tianzhang; Weinberger, Daniel R.; Kleinman, Joel E.; Hyde, Thomas M. (PLOS ONE, 2016)
Genetic variation and early adverse environmental events work together to increase risk for schizophrenia. γ-aminobutyric acid (GABA), the major inhibitory neurotransmitter in adult mammalian brain, plays a major role in normal brain development, and has been strongly implicated in the pathobiology of schizophrenia. GABA synthesis is controlled by two glutamic acid decarboxylase (GAD) genes, GAD1 and GAD2, both of which produce a number of alternative transcripts. Genetic variants in the GAD1 gene are associated with increased risk for schizophrenia, and reduced expression of its major transcript in the human dorsolateral prefrontal cortex (DLPFC). No consistent changes in GAD2 expression have been found in brains from patients with schizophrenia. In this work, with the use of RNA sequencing and PCR technologies, we confirmed and tracked the expression of an alternative truncated transcript of GAD2 (ENST00000428517) in human control DLPFC homogenates across lifespan besides the well-known full length transcript of GAD2. In addition, using quantitative RT-PCR, expression of GAD2 full length and truncated transcripts were measured in the DLPFC of patients with schizophrenia, bipolar disorder and major depression. The expression of GAD2 full length transcript is decreased in the DLPFC of schizophrenia and bipolar disorder patients, while GAD2 truncated transcript is increased in bipolar disorder patients but decreased in schizophrenia patients. Moreover, the patients with schizophrenia with completed suicide or positive nicotine exposure showed significantly higher expression of GAD2 full length transcript. Alternative transcripts of GAD2 may be important in the growth and development of GABA-synthesizing neurons as well as abnormal GABA signaling in the DLPFC of patients with schizophrenia and affective disorders.